Current Development in Lead-Free Bi0.5(Na,K)0.5TiO3-Based Piezoelectric Materials - Ngo Duc Quan; Luong Huu Bac; Duong Van Thiet; Vu Ngoc Hung; Dang Duc Dung (Advances in Materials Science and Engineering)
The lead-free piezoelectric ceramics display good piezoelectric properties which are comparable with Pb(Zr,Ti)O3 (PZT) and these materials overcome the hazard to the environment and human health. The Bi0.5(Na,K)0.5TiO3 (BNKT) is rapidly developed because of good piezoelectric, ferroelectric, and dielectric properties compared to PZT. The origin of giant strain of BNKT piezoelectric materials was found at morphotropic phase boundary due to crystal change from tetragonal to orthorhombic and/or precipitation of cubic phases, in addition to domain switching mechanism. The dopants or secondary phases with ABO3 structure as solid solution are expected to change the crystal structure and create the vacancies which results in enhancement of the piezoelectric properties. In this work, we reviewed the current development of BNKT by dopants and secondary phase as solid solution. Our discussion will focus on role of dopants and secondary phase to piezoelectric properties of BNKT. This result will open the direction to control the properties of lead-free piezoelectric materials.